pH-responsive integrated fracturing flowback fluid treatment agent and application thereof

CN122897573APending Publication Date: 2026-10-13QINGDAO BAILIDA ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611402587.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0002]压裂返排液中常含有胍胶等高分子残留物、乳化油、悬浮物和无机盐,水体黏度较高,乳化和胶体结构稳定,仅采用单一氧化或絮凝工艺难以同时兼顾有机物降解、除油、除悬浮物及后续固液分离

Benefits of technology

[0024]与现有技术相比,本发明将酸化破乳、亚铁活化过硫酸盐氧化、中性至碱性凝结和聚合物絮凝安排在不同pH阶段,酸性药剂和碱性药剂不会在投加时直接中和,氧化剂、亚铁盐和絮凝剂也不会在处理开始时一次性接触。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of oilfield wastewater treatment, and particularly relates to a pH-responsive integrated fracturing flowback fluid treatment agent and application thereof. The treatment agent comprises acidification components, persulfate, ferrous salt, alkalization components and flocculation components stored respectively. When used, the fracturing flowback fluid is first adjusted to be acidic to perform demulsification and activate oxidation, then the pH is adjusted back to neutral to alkaline, so that iron ions are hydrolyzed and inorganic particles are coagulated in situ, and then flocculation separation is performed; the ferrous salt and the flocculation components can also be simultaneously replaced by a premixed iron-polymer composite liquid. The treatment agent can reduce the viscosity, COD, oil content and suspended solids content of the fracturing flowback fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oilfield wastewater treatment technology, specifically to a pH-responsive integrated fracturing flowback fluid treatment agent and its application. Background Technology

[0002] Fracturing flowback fluids often contain high molecular weight residues such as guar gum, emulsified oil, suspended solids, and inorganic salts. The water has high viscosity and stable emulsion and colloidal structures. It is difficult to simultaneously achieve organic matter degradation, oil removal, suspended solids removal, and subsequent solid-liquid separation using only a single oxidation or flocculation process.

[0003] CN116986748A discloses an oxidation treatment method for oilfield fracturing flowback fluid, which involves first adjusting the pH and adding a transition metal catalyst, then adding persulfate for oxidation, followed by treatment with a flocculant and pressure filtration separation. CN117263358A discloses a viscosity-reducing synergist composed of dendritic polyamide-amine macromolecular compounds, solid acids, and ferrous salts, used to activate persulfate at room temperature and reduce the viscosity of high-viscosity fracturing wastewater. CN109052616A discloses a method for coordinating citric acid to regulate the activation of persulfate by ferrous ions, adjusting the concentration of free ferrous ions through pH and material ratio to treat organic pollutants.

[0004] The aforementioned technologies focus on oxidation treatment, rapid viscosity reduction, or ferrous coordination regulation, respectively. Treatment of fracturing flowback fluid still requires coordination of each stage: demulsification, oxidative degradation, pH adjustment, inorganic precipitation, and polymer flocculation. This is to reduce mutual interference caused by simultaneous contact of acid and alkali components, ferrous salts, persulfates, and flocculants, and to improve the simultaneous removal of multiple contaminants and the solid-liquid separation effect. Summary of the Invention

[0005] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a fracturing flowback fluid treatment scheme that achieves continuous demulsification, oxidation, coagulation and flocculation by staged pH control and sequential addition of reagents.

[0006] To achieve the above objectives, this invention provides a pH-responsive integrated fracturing flowback fluid treatment agent, comprising independently stored acidifying, oxidizing, activating, alkalizing, and flocculating components; the acidifying component is an 8%-12% (w / w) citric acid aqueous solution, the oxidizing component is ammonium persulfate, the activating component is ferrous sulfate heptahydrate, the mass ratio of ammonium persulfate to ferrous sulfate heptahydrate is 4-6:1, the alkalizing component comprises anhydrous sodium carbonate and an 8%-12% (w / w) sodium hydroxide aqueous solution, and the flocculant component is an anionic polyacrylamide solution; the concentration of the anionic polyacrylamide solution is 0.8-1.2 g / L.

[0007] In one embodiment, the citric acid aqueous solution has a mass fraction of 10%.

[0008] In one embodiment, the mass ratio of ammonium persulfate to ferrous sulfate heptahydrate is 5:1.

[0009] In one embodiment, the sodium hydroxide aqueous solution has a mass fraction of 10%.

[0010] In one embodiment, the anionic polyacrylamide has a weight-average molecular weight of 12 million and a degree of hydrolysis of 25%-30%; the concentration of the anionic polyacrylamide solution is 1.0 g / L.

[0011] This invention utilizes pH changes during the treatment process to define the action stages of each component. Acidic conditions disrupt emulsification and colloidal stability, and provide a reaction environment for the activation of ammonium persulfate by ferrous sulfate heptahydrate. After oxidation, the water is adjusted to neutral to alkaline, causing iron ions to hydrolyze and some inorganic ions to form fine precipitates. Anionic polyacrylamide then promotes the formation of settleable flocs from the colloidal particles and fine precipitates. Storing each component separately and adding them sequentially reduces interference between acidification, alkalization, oxidation, and flocculation.

[0012] This invention also provides the application of the pH-responsive integrated fracturing flowback fluid treatment agent in fracturing flowback fluid treatment, comprising the following steps:

[0013] 1) Acidification demulsification: Add citric acid aqueous solution to the fracturing flowback fluid, adjust the pH to 3.0-4.0, and stir for 10-15 minutes;

[0014] 2) Oxidative degradation: Add ammonium persulfate and ferrous sulfate heptahydrate to the acidified fracturing flowback fluid and react at 20-30℃ for 30-45 min.

[0015] 3) Neutralization and adjustment: First, add anhydrous sodium carbonate to the oxidized fracturing flowback fluid, then add sodium hydroxide aqueous solution to adjust the pH to 7.0-9.0;

[0016] 4) Flocculation separation: Add anionic polyacrylamide solution to the neutralized fracturing flowback fluid, and perform rapid stirring, slow stirring and static sedimentation in sequence to separate the supernatant.

[0017] In another embodiment, a premixed iron-polymer composite liquid is used to simultaneously replace the independently added ferrous sulfate heptahydrate and anionic polyacrylamide, i.e., the treatment agent does not separately contain ferrous salt components and flocculants; in the oxidation stage, the premixed iron-polymer composite liquid provides ferrous ions and participates in the activation of persulfate, and in the flocculation stage, the copolymer in the premixed iron-polymer composite liquid provides adsorption bridging.

[0018] The premixed iron-polymer composite liquid is prepared by premixing a pH-responsive copolymer containing carboxyl, amide, and tertiary amine groups with ferrous ions.

[0019] During the acidic oxidation stage, the composite solution can be used to provide ferrous ions and participate in the activation of persulfate; after the pH is adjusted to neutral to alkaline, ferrous ions hydrolyze and participate in coagulation and flocculation; its role may be related to the interaction between ferrous ions and copolymers at different pH levels.

[0020] In one embodiment, the pH-responsive copolymer is polymerized from acrylamide, acrylic acid, and 2-(dimethylamino)ethyl methacrylate in a mass ratio of 7.5:1.5:1.0. Further preferably, the preparation method of the pH-responsive copolymer is as follows: acrylamide, acrylic acid, and 2-(dimethylamino)ethyl methacrylate are added to deionized water at a mass ratio of 7.5:1.5:1.0, and stirred at 150-250 rpm until all monomers are completely dissolved to obtain a monomer mixture; the pH of the monomer mixture is adjusted to 5.5-6.5 using a sodium hydroxide aqueous solution, and nitrogen gas is purged for 30-60 min to remove dissolved oxygen; the reaction system temperature is adjusted to 25-35℃, and ammonium persulfate and sodium bisulfite are added to the monomer mixture, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 4:3, and the total amount of ammonium persulfate and sodium bisulfite is 0.2%-0.5% of the total mass of monomers; the reaction is carried out at 25-35℃ and 100-200 rpm for 3-5 minutes. h; After the reaction is complete, the obtained polymer solution is slowly added to anhydrous ethanol at 3-8 times its volume to precipitate the polymer. The polymer precipitate is collected by filtration, washed 2-4 times with anhydrous ethanol, and vacuum dried to constant weight at 40-50℃. The polymer is then pulverized and sieved to obtain a pH-responsive copolymer with a particle size of 100-400 μm.

[0021] In one embodiment, the premixed iron-polymer composite solution is prepared by the following method: a pH-responsive copolymer is added to nitrogen-deoxygenated deionized water, and stirred at 100-200 rpm for 20-40 min to allow the copolymer to swell and disperse, obtaining a copolymer dispersion; ferrous sulfate heptahydrate is dissolved in nitrogen-deoxygenated deionized water to prepare a ferrous sulfate heptahydrate aqueous solution; under nitrogen protection, the ferrous sulfate heptahydrate aqueous solution is added dropwise to the copolymer dispersion at a rate of 0.2-1.0 mL / min, and after the addition is completed, stirring is continued at 20-30°C for 30-90 min to obtain the premixed iron-polymer composite solution; in the premixed iron-polymer composite solution, the mass concentration of the pH-responsive copolymer is 1.5-2.5 g / L, and the mass concentration of ferrous sulfate heptahydrate is 30-50 g / L. Preferably, the premixed iron-polymer composite liquid contains a pH-responsive copolymer with a mass concentration of 2.0 g / L and ferrous sulfate heptahydrate with a mass concentration of 40.0 g / L, and is used within 24 h after preparation.

[0022] In one embodiment, in step 2), 3-5 g of ammonium persulfate and 20-30 mL of the premixed iron-polymer composite solution are added to every 1 L of fracturing flowback fluid; in the premixed iron-polymer composite solution, the mass concentration of the pH-responsive copolymer is 1.5-2.5 g / L, and the mass concentration of ferrous sulfate heptahydrate is 30-50 g / L.

[0023] The beneficial effects of this invention are:

[0024] Compared with the prior art, the present invention arranges acidification demulsification, ferrous activated persulfate oxidation, neutral to alkaline coagulation and polymer flocculation at different pH stages. The acidic and alkaline agents will not be directly neutralized at the time of addition, and the oxidant, ferrous salt and flocculant will not come into contact at the beginning of the treatment.

[0025] Compared to treatment methods that only involve oxidation or flocculation, this invention utilizes the continuous effects of oxidation chain scission, iron ion hydrolysis, inorganic particle precipitation, and polymer bridging to simultaneously reduce the viscosity, COD, oil content, and suspended solids content of fracturing flowback fluid.

[0026] Compared to the method of adding all the reagents at once, this invention retains the reaction conditions required for both the acidic oxidation stage and the neutral to alkaline flocculation stage, which is beneficial to improving reagent utilization and forming a clear mud-water interface.

[0027] This invention employs a treatment agent that is stored separately and added in stages. The dosage of the agent can be adjusted according to the pollution load and real-time pH of the fracturing flowback fluid, making it convenient to complete demulsification, oxidation, coagulation and flocculation separation in the same treatment unit. Detailed Implementation

[0028] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0029] Unless otherwise stated, all percentages mentioned below are by weight.

[0030] Anionic polyacrylamide, with a weight-average molecular weight of approximately 12 million and a degree of hydrolysis of 25%-30%, brand name: AN 926SHU.

[0031] Example 1

[0032] A method for preparing a pH-responsive integrated fracturing flowback fluid treatment agent includes the following steps:

[0033] 1) Weigh 10.0 g of citric acid, add it to 90.0 g of deionized water, and stir until completely dissolved to obtain a 10% citric acid aqueous solution;

[0034] 2) Weigh 10.0 g of sodium hydroxide and add it to 90.0 g of deionized water while stirring and cooling. After the sodium hydroxide is completely dissolved and the solution is cooled to room temperature, a sodium hydroxide aqueous solution with a mass fraction of 10% is obtained.

[0035] 3) Add deionized water to the preparation container, and add anionic polyacrylamide while stirring at 200 rpm to make the concentration of anionic polyacrylamide 1.0 g / L; continue stirring and maturing for 60 min until the anionic polyacrylamide is completely swollen and there are no fish-eye particles in the solution, thus obtaining an anionic polyacrylamide solution.

[0036] 4) Weigh out 0.5 g of ammonium persulfate, 0.1 g of ferrous sulfate heptahydrate and 0.5 g of anhydrous sodium carbonate respectively; store ammonium persulfate, ferrous sulfate heptahydrate and anhydrous sodium carbonate separately to avoid contact reaction before use; wherein, the mass ratio of ammonium persulfate to ferrous sulfate heptahydrate is 5:1.

[0037] The above-mentioned citric acid aqueous solution, sodium hydroxide aqueous solution, anionic polyacrylamide solution, ammonium persulfate, ferrous sulfate heptahydrate and anhydrous sodium carbonate were stored independently and together formed the pH-responsive integrated fracturing flowback fluid treatment agent of Example 1.

[0038] The specific applications of the treatment agent are as follows:

[0039] The pH-responsive integrated fracturing flowback fluid treatment agent is used to treat fracturing flowback fluid, specifically including the following steps:

[0040] The fracturing flowback fluid is a pale yellow, slightly turbid liquid with an initial pH of 7.2, a viscosity of 4.21 mPa·s, a COD of 3587 mg / L, an oil content of 110 mg / L, a suspended solids content of 320 mg / L, and a guar gum content of 1765 mg / L.

[0041] S1 was mechanically stirred at 25℃ with the stirring speed adjusted to 300 rpm. 0.5 mL of 10% citric acid aqueous solution was added dropwise to 100 mL of fracturing flowback fluid at a uniform rate to lower the pH of the system to 3.0. Stirring was continued at 300 rpm for 10 min. As the pH decreased, the emulsification stability of the fracturing flowback fluid was disrupted, and the system gradually changed from a uniform microemulsion state to a slight stratification.

[0042] S2 adjusted the stirring speed to 200 rpm, added 0.5 g of ammonium persulfate to the acidified system, and then slowly added 0.1 g of ferrous sulfate heptahydrate in batches; reacted at 25℃ and 200 rpm for 30 min; during the reaction, the color of the system first darkened and then gradually lightened, accompanied by the generation of a small number of tiny bubbles; the stabilization of the redox potential of the system was used as the basis for judging that the oxidation reaction was basically completed.

[0043] During this stage, ferrous sulfate heptahydrate activates ammonium persulfate to produce oxidizing active species, which break down and degrade guar gum and other polymers remaining in the fracturing flowback fluid; citric acid may also complex with ferrous ions, which helps to regulate the contact and reaction rate between ferrous ions and persulfate.

[0044] After the S3 oxidation reaction is completed, 0.5 g of anhydrous sodium carbonate is slowly added to the system in multiple portions while stirring. Since sodium carbonate produces carbon dioxide gas and releases heat when it reacts with an acidic system, it is added in small amounts multiple times. The system temperature is controlled to not exceed 30°C by using a cooling water bath to avoid violent bubbling or liquid overflow. After the sodium carbonate is added, 1.0 mL of a 10% sodium hydroxide aqueous solution is slowly added dropwise to fine-tune the pH of the system so that the pH of the system is 7.9 at the end of the addition.

[0045] As the system changes from acidic to slightly alkaline, some calcium, magnesium, and metal ions in the system form fine precipitates of carbonates or hydroxides; the ferric ions generated during the oxidation stage undergo hydrolysis, forming ferric hydroxide colloidal particles in situ.

[0046] S4. Add 0.5 mL of 1.0 g / L anionic polyacrylamide solution to the neutralized system. First, stir rapidly at 200 rpm for 1 min to ensure that the anionic polyacrylamide comes into full contact with the colloidal particles and fine precipitates in the water. Then, reduce the stirring speed to 50 rpm and stir slowly for 5 min to allow the fine particles to gradually form larger flocs through adsorption bridging and sweeping. Stop stirring and allow the mixture to stand at 25°C for 30 min to settle. After settling, a clear mud-water interface appears in the system, with dense flocs forming at the bottom and the upper water layer becoming significantly clear. Use a pipette to slowly aspirate the supernatant from 2 cm below the liquid surface, avoiding disturbing the bottom sediment, and then analyze the supernatant.

[0047] The resulting supernatant had a pH of 8.1, a viscosity of 1.10 mPa·s, a COD of 75 mg / L, an oil content of 3.0 mg / L, a suspended solids content of 6.7 mg / L, a guar gum content of 36.5 mg / L, and a residual persulfate content of 14.6 mg / L.

[0048] Example 2

[0049] The raw materials and preparation methods of each treatment component used in this embodiment are the same as in Example 1. A 10% (w / w) citric acid aqueous solution, a 10% (w / w) sodium hydroxide aqueous solution, a 1.0 g / L anionic polyacrylamide solution, as well as ammonium persulfate, ferrous sulfate heptahydrate, and anhydrous sodium carbonate were stored separately.

[0050] The pH-responsive integrated fracturing flowback fluid treatment agent is used to treat a moderately contaminated fracturing flowback fluid, and specifically includes the following steps:

[0051] Take 100 mL of a moderately polluted fracturing flowback fluid; the fracturing flowback fluid is pale yellow and slightly turbid, with an initial pH of 6.8, a viscosity of 4.34 mPa·s, a COD of 3879 mg / L, a suspended solids content of 519 mg / L, and an oil content of 150 mg / L.

[0052] S1 was mechanically stirred at 300 rpm at 25℃, and 0.8 mL of 10% citric acid aqueous solution was added dropwise to the fracturing flowback fluid at a uniform rate to adjust the pH of the system to 3.0; stirring was continued for 15 min, and slight stratification of the system occurred.

[0053] S2 adjusted the stirring speed to 200 rpm, added 0.3 g of ammonium persulfate, and then added 0.06 g of ferrous sulfate heptahydrate in batches; the reaction was carried out at 25℃ for 38 min, and the color of the system changed from dark to light and tended to stabilize;

[0054] S3 added 0.8 g of anhydrous sodium carbonate to the oxidized system in multiple portions, and used a cooling water bath to control the system temperature below 30℃; after the anhydrous sodium carbonate was added, 1.5 mL of a 10% sodium hydroxide aqueous solution was slowly added dropwise to adjust the pH of the system to 7.9.

[0055] S4 added 0.5 mL of 1.0 g / L anionic polyacrylamide solution to the neutralized system, first stirred rapidly at 200 rpm for 1 min, then stirred slowly at 50 rpm for 5 min; then allowed to stand at 25℃ for 30 min to precipitate, and used a pipette to draw the supernatant from 2 cm below the liquid surface for detection.

[0056] The resulting supernatant had a pH of 7.9, a viscosity of 1.54 mPa·s, a COD of 280 mg / L, an oil content of 6.8 mg / L, and a suspended solids content of 16.3 mg / L.

[0057] Example 3

[0058] The raw materials and preparation methods of each treatment component used in this embodiment are the same as in Example 1. A 10% (w / w) citric acid aqueous solution, a 10% (w / w) sodium hydroxide aqueous solution, a 1.0 g / L anionic polyacrylamide solution, as well as ammonium persulfate, ferrous sulfate heptahydrate, and anhydrous sodium carbonate were stored separately.

[0059] The pH-responsive integrated fracturing flowback fluid treatment agent is used to treat a highly polluted fracturing flowback fluid, and specifically includes the following steps:

[0060] Take 100 mL of a highly polluting fracturing flowback fluid; the initial pH of the fracturing flowback fluid is 7.2, the viscosity is 4.53 mPa·s, the COD is 4200 mg / L, the suspended solids content is 683.2 mg / L, and the oil content is 230 mg / L.

[0061] S1 was mechanically stirred at 200 rpm at 25℃, and 1.0 mL of 10% citric acid aqueous solution was added dropwise to the fracturing flowback fluid at a uniform rate to adjust the pH of the system to 4.0; stirring was continued for 10 min, and slight stratification of the system occurred.

[0062] S2 was added with 0.5 g of ammonium persulfate, followed by 0.1 g of ferrous sulfate heptahydrate in portions. The reaction was carried out at 25 °C and 200 rpm for 45 min, and the color of the system changed from dark to light and tended to stabilize.

[0063] S3 added 1.0 g of anhydrous sodium carbonate to the oxidized system in several portions, and used a cooling water bath to control the system temperature below 30°C; then slowly added 1.8 mL of a 10% sodium hydroxide aqueous solution, and continued stirring until the pH of the system stabilized at 7.9;

[0064] S4 added 0.5 mL of 1.0 g / L anionic polyacrylamide solution to the neutralized system, first stirred rapidly at 200 rpm for 1 min, then stirred slowly at 50 rpm for 5 min; then allowed to stand at 25℃ for 30 min to precipitate, and used a pipette to draw the supernatant from 2 cm below the liquid surface for detection.

[0065] The resulting supernatant had a pH of 7.9, a viscosity of 1.32 mPa·s, a COD of 350 mg / L, an oil content of 19.67 mg / L, and a suspended solids content of 28.4 mg / L.

[0066] Example 4

[0067] A method for preparing a pH-responsive integrated fracturing flowback fluid treatment agent includes the following steps:

[0068] 1) Weigh 10.0 g of citric acid, add it to 90.0 g of deionized water, and stir until completely dissolved to obtain a 10% citric acid aqueous solution;

[0069] 2) Weigh 10.0 g of sodium hydroxide and slowly add it to 90.0 g of deionized water while stirring and cooling. After the sodium hydroxide is completely dissolved and the solution is cooled to room temperature, a 10% sodium hydroxide aqueous solution is obtained.

[0070] 3) Add 90.0 g of deionized water to a reaction vessel equipped with a mechanical stirrer, thermometer, and nitrogen delivery tube. Then add 7.5 g of acrylamide, 1.5 g of acrylic acid, and 1.0 g of 2-(dimethylamino)ethyl methacrylate sequentially. Stir at 200 rpm until all monomers are completely dissolved to obtain a monomer mixture. Adjust the pH of the monomer mixture to 6.0 using a 10% sodium hydroxide aqueous solution. Then purge with nitrogen for 30 min to remove dissolved oxygen from the monomer mixture. Adjust the reaction temperature to 30℃. Add 2.0 mL of a 10 g / L ammonium persulfate aqueous solution and 1.5 mL of a 10 g / L sodium bisulfite aqueous solution to the monomer mixture. React at 30℃ and 150 rpm for 4 minutes. h; After the reaction is complete, the obtained polymer solution is slowly added to anhydrous ethanol 5 times its volume to precipitate the polymer; the polymer precipitate is collected by filtration, washed 3 times with anhydrous ethanol, vacuum dried at 40°C to constant weight, pulverized and sieved to obtain a pH-responsive copolymer with a particle size of 150-300 μm.

[0071] In the pH-responsive copolymer, the acrylamide structural unit provides long-chain adsorption bridging, the acrylic acid structural unit provides carboxyl coordination sites, and the 2-(dimethylamino)ethyl methacrylate structural unit provides tertiary amine pH-responsive sites.

[0072] Add 20 mL of nitrogen-deoxygenated deionized water to a coordination reaction vessel, add 0.050 g of the pH-responsive copolymer, and stir at 150 rpm for 30 min to allow the copolymer to fully swell and disperse. Separately, take 5 mL of nitrogen-deoxygenated deionized water, add 1.00 g of ferrous sulfate heptahydrate, and stir until completely dissolved to obtain an aqueous solution of ferrous sulfate heptahydrate. Under nitrogen protection and stirring at 150 rpm, add the ferrous sulfate heptahydrate aqueous solution dropwise to the pH-responsive copolymer dispersion at a rate of 0.5 mL / min. After the addition is complete, continue stirring at 25°C for 60 min to ensure sufficient contact between the ferrous ions and the copolymer, resulting in a premixed iron-polymer composite solution with a total volume of approximately 25 mL. In the obtained premixed iron-polymer composite solution, the mass concentration of the pH-responsive copolymer is approximately 2.0 g / L, and the mass concentration of ferrous sulfate heptahydrate is approximately 40.0 g / L. Seal and protect the premixed iron-polymer composite solution from light, and use it within 24 h after preparation.

[0073] 4) Prepare 0.5 g of ammonium persulfate and 0.5 g of anhydrous sodium carbonate respectively.

[0074] The pH-responsive integrated fracturing flowback fluid treatment agent is used to treat fracturing flowback fluid, specifically including the following steps:

[0075] The initial pH of the fracturing flowback fluid was 7.2, the viscosity was 4.21 mPa·s, the COD was 3587 mg / L, the oil content was 110 mg / L, the suspended solids content was 320 mg / L, and the guar gum content was 1765 mg / L.

[0076] S1 was mechanically stirred at 300 rpm at 25℃, and 0.5 mL of 10% citric acid aqueous solution was added dropwise at a uniform rate to adjust the pH of the system to 3.0; stirring was continued at 300 rpm for 10 min to allow the emulsified oil droplets and colloidal particles to undergo acidification and destabilization until the system showed slight stratification.

[0077] S2 adjusted the stirring speed to 200 rpm and added 0.5 g of ammonium persulfate to the acidified fracturing flowback fluid, stirring for 1 min to ensure uniform dispersion of the ammonium persulfate. Then, 2.5 mL of a premixed iron-polymer composite solution was added at a rate of 0.5 mL / min. The added iron-polymer composite solution contained approximately 0.005 g of pH-responsive copolymer and 0.100 g of ferrous sulfate heptahydrate. The reaction was carried out at 25°C and 200 rpm for 30 min. This premixed iron-polymer composite solution provides ferrous ions and activates ammonium persulfate under acidic conditions, which is used to degrade guar gum and other organic polymeric contaminants in the fracturing flowback fluid. During the reaction, the system color first deepened and then gradually lightened, accompanied by the generation of a small number of tiny bubbles. After 30 min of reaction, the redox potential of the system tended to stabilize.

[0078] After the S3 oxidation reaction was completed, 0.5 g of anhydrous sodium carbonate was added to the system in 5 portions, each time 0.1 g, with a 1-minute interval between each addition, under stirring at 200 rpm. During the addition process, a cooling water bath was used to control the system temperature to not exceed 30°C. After the anhydrous sodium carbonate was added, 1.0 mL of a 10% sodium hydroxide aqueous solution was slowly added dropwise to adjust the pH of the system to 8.0. As the system changed from acidic to slightly alkaline, the ferric ions formed in the oxidation stage underwent hydrolysis, forming fine colloidal particles of ferric hydroxide. These particles, together with the copolymer, participated in subsequent coagulation and flocculation. The mechanism may be related to the interaction between ferric ions and the copolymer at different pH levels.

[0079] After the pH of the S4 system stabilized at 8.0, it was continuously stirred rapidly at 200 rpm for 1 min to ensure sufficient contact between the iron-polymer composite coagulation nuclei and oil droplets, suspended matter, and organic degradation products. Subsequently, the stirring speed was reduced to 50 rpm and stirred slowly for 5 min to allow the fine particles to form larger flocs under the adsorption bridging effect of the copolymer. Stirring was stopped, and the mixture was allowed to settle at 25°C for 30 min. After about 6 min of settling, a clear mud-water interface appeared. After 30 min of settling, a dense floc structure formed at the bottom, and the upper water was clear. The supernatant was taken from 2 cm below the liquid surface using a pipette for analysis.

[0080] The test results showed that the obtained supernatant had a pH of 8.0, a viscosity of 1.02 mPa·s, a COD of 48 mg / L, an oil content of 1.8 mg / L, a suspended solids content of 3.9 mg / L, a guar gum content of 21.8 mg / L, and a residual persulfate content of 6.8 mg / L.

[0081] Comparative Example

[0082] All comparative examples below use the same batch of fracturing flowback fluid as in Example 1, with a treatment volume of 100 mL. Except for explicitly changed treatment conditions, the dosage of each reagent, reaction temperature, stirring conditions, standing time, and sampling method are the same as in Example 1.

[0083] Comparative Example 1

[0084] The only difference between this comparative example and Example 1 is that the acidification and demulsification treatment is not performed; all other conditions are the same. Specifically, the steps are as follows:

[0085] S1 Take 100 mL of the fracturing flowback fluid used in Example 1, without adding citric acid aqueous solution;

[0086] S2 added 0.5 g of ammonium persulfate to the fracturing flowback fluid, followed by 0.1 g of ferrous sulfate heptahydrate, and reacted for 30 min at 25 °C and 200 rpm.

[0087] S3 was added sequentially with 0.5 g of anhydrous sodium carbonate and 1.0 mL of 10% sodium hydroxide aqueous solution. Since this comparative example did not undergo acidification and demulsification, the initial pH of the system was close to neutral. After the addition of the alkalizing component, the pH of the system increased further. The pH of the system was measured to be 9.5 after the addition was completed.

[0088] Add 0.5 mL of 1.0 g / L anionic polyacrylamide solution to S4, stir rapidly at 200 rpm for 1 min, then stir slowly at 50 rpm for 5 min, and then let it stand at 25℃ for 30 min to precipitate.

[0089] The obtained supernatant had a viscosity of 2.56 mPa·s, a COD of 1286 mg / L, an oil content of 89.9 mg / L, and a suspended solids content of 45.87 mg / L.

[0090] Comparative Example 2

[0091] The only difference between this comparative example and Example 1 is that ammonium persulfate is not added; all other conditions are the same. Specifically, the steps are as follows:

[0092] S1 Take 100 mL of the fracturing flowback fluid used in Example 1, add 0.5 mL of 10% citric acid aqueous solution, adjust the pH of the system to 3.0, and stir for 10 min at 25℃ and 300 rpm.

[0093] S2 added 0.1 g of ferrous sulfate heptahydrate to the acidified system, without adding ammonium persulfate, and stirred for 30 min at 25°C and 200 rpm.

[0094] S3 is prepared by adding 0.5 g of anhydrous sodium carbonate and 1.0 mL of 10% sodium hydroxide aqueous solution to adjust the pH of the system to 7.9.

[0095] S4 was added to 0.5 mL of a 1.0 g / L anionic polyacrylamide solution, and flocculation separation was carried out according to the stirring and settling conditions of Example 1.

[0096] The obtained supernatant had a viscosity of 2.47 mPa·s, a COD of 1564 mg / L, an oil content of 18.2 mg / L, and a suspended solids content of 54.87 mg / L.

[0097] Comparative Example 3

[0098] The only difference between this comparative example and Example 1 is that pH adjustment is not performed after the oxidation reaction; all other conditions are the same. Specifically, the steps are as follows:

[0099] S1 Take 100 mL of the fracturing flowback fluid used in Example 1, add 0.5 mL of 10% citric acid aqueous solution, adjust the pH of the system to 3.0, and stir for 10 min at 25℃ and 300 rpm.

[0100] S2 was added with 0.5 g of ammonium persulfate and 0.1 g of ferrous sulfate heptahydrate, and reacted at 25 °C and 200 rpm for 30 min.

[0101] After the S3 oxidation reaction is completed, no anhydrous sodium carbonate or sodium hydroxide aqueous solution is added;

[0102] S4 directly adds 0.5 mL of 1.0 g / L anionic polyacrylamide solution to the acidic system, first stirs rapidly at 200 rpm for 1 min, then stirs slowly at 50 rpm for 5 min, and then allows to stand at 25℃ for 30 min to precipitate.

[0103] The obtained supernatant had a viscosity of 2.05 mPa·s, a COD of 764 mg / L, an oil content of 27.5 mg / L, and a suspended solids content of 56.98 mg / L.

[0104] Comparative Example 4

[0105] The only difference between this comparative example and Example 1 is that anionic polyacrylamide is not added; all other conditions are the same. Specifically, the steps are as follows:

[0106] S1 Take 100 mL of the fracturing flowback fluid used in Example 1, add 0.5 mL of 10% citric acid aqueous solution, adjust the pH of the system to 3.0, and stir for 10 min at 25℃ and 300 rpm.

[0107] S2 was added with 0.5 g of ammonium persulfate and 0.1 g of ferrous sulfate heptahydrate, and reacted at 25 °C and 200 rpm for 30 min.

[0108] S3 is prepared by adding 0.5 g of anhydrous sodium carbonate and 1.0 mL of 10% sodium hydroxide aqueous solution to adjust the pH of the system to 7.9.

[0109] S4 was prepared without the addition of anionic polyacrylamide, stirred at 50 rpm for 5 min, and then allowed to stand at 25°C for 30 min to precipitate.

[0110] The obtained supernatant had a viscosity of 1.56 mPa·s, a COD of 256 mg / L, an oil content of 46.3 mg / L, and a suspended solids content of 65.7 mg / L.

[0111] Comparative Example 5

[0112] The only difference between this comparative example and Example 1 is that all the reagents are added to the fracturing flowback fluid at once, without stepwise pH adjustment and sequential addition; all other conditions are the same. Specifically, the steps are as follows:

[0113] Take 100 mL of the fracturing flowback fluid used in Example 1, and simultaneously add 0.5 mL of 10% citric acid aqueous solution, 0.5 g of ammonium persulfate, 0.1 g of ferrous sulfate heptahydrate, 0.5 g of anhydrous sodium carbonate, 1.0 mL of 10% sodium hydroxide aqueous solution, and 0.5 mL of 1.0 g / L anionic polyacrylamide solution;

[0114] Stir at 25°C and 200 rpm for 30 min, then stir at 50 rpm for 5 min, and then let stand to settle for 30 min.

[0115] The obtained supernatant had a viscosity of 3.75 mPa·s, a COD of 2976 mg / L, an oil content of 32.9 mg / L, and a suspended solids content of 123.2 mg / L.

[0116] Comparative Example 6

[0117] The only difference between this comparative example and Example 4 is that a premixed iron-polymer composite solution is not prepared beforehand; instead, equal amounts of ferrous sulfate heptahydrate and a pH-responsive copolymer are added to the treatment system, while all other conditions remain the same. Specifically, the steps include:

[0118] S1 Take 100 mL of the same batch of fracturing flowback fluid as in Example 4, and perform acidification and demulsification according to step S1 of Example 4.

[0119] S2 added 0.5 g of ammonium persulfate to the acidified system, stirred for 1 min, and then directly added 0.100 g of ferrous sulfate heptahydrate and 0.005 g of the pH-responsive copolymer prepared in step 3) of Example 4. The mixture was reacted at 25°C and 200 rpm for 30 min.

[0120] S3 and S4 are performed according to steps S3 and S4 of Example 4, including pH adjustment, coagulation, slow flocculation and static separation.

[0121] The test results showed that the obtained supernatant had a pH of 8.0, a viscosity of 1.18 mPa·s, a COD of 92 mg / L, an oil content of 4.6 mg / L, a suspended solids content of 9.8 mg / L, a guar gum content of 48.7 mg / L, and a residual persulfate content of 21.5 mg / L.

[0122] Test Example 1

[0123] Treatment effects of fracturing flowback fluid with different levels of contamination

[0124] The fracturing flowback fluid before treatment and the supernatant after treatment in Examples 1-3 were tested respectively.

[0125] pH was measured according to GB / T 6920-1986 "Determination of pH in Water - Glass Electrode Method", using a pH meter calibrated with a standard buffer solution. Each water sample was measured in triplicate, and the average value was taken.

[0126] Viscosity was measured in accordance with GB / T 10247-2008 "Methods for Viscosity Measurement". A Shanghai Yetuo NDJ-8S rotational viscometer was used with rotor No. 0 to measure the viscosity of the water sample at 60 rpm and 25℃. The effective measurement range of the rotor and rotation speed configuration is 1-10 mPa·s. The viscosity of the water sample was estimated before measurement and the reading was confirmed to be within the effective range.

[0127] COD testing was conducted according to HJ 828-2017 "Determination of Chemical Oxygen Demand in Water - Dichromate Method". For untreated water samples with high COD, appropriate dilution was performed first to ensure the measured value was within the effective range of this method. Since the chloride ion concentration in fracturing flowback fluid may be high, the chloride ion concentration in the water sample was first determined according to GB / T 11896-1989 "Determination of Chloride in Water - Silver Nitrate Titration Method". When the chloride ion concentration in the water sample exceeded 1000 mg / L, the COD was determined according to HJ 70-2025 "Determination of Chemical Oxygen Demand in Water - Chlorine Correction Method".

[0128] For oil content detection, the determination principle of HJ 637-2018 "Determination of Petroleum and Animal Oils in Water Quality - Infrared Spectrophotometry" was followed, and the sample size was reduced proportionally for this test. 25 mL of water sample was placed in a 125 mL separatory funnel, and hydrochloric acid was added to adjust the pH of the water sample to below 2. The sample was then thoroughly mixed.

[0129] Add 15 mL of tetrachloroethylene to the separatory funnel, shake vigorously for 2 min, and let stand for 5 min. Separate the lower tetrachloroethylene phase and store it temporarily. Extract the upper aqueous phase again with 5 mL of tetrachloroethylene. Combine the two tetrachloroethylene phases, dehydrate them through a sintered funnel filled with 1.0 cm thick anhydrous sodium sulfate, and collect them in a 25 mL volumetric flask.

[0130] Combine the two tetrachloroethylene extraction phases and bring the volume to the mark with tetrachloroethylene.

[0131] Using the same batch of tetrachloroethylene as a reference, an infrared spectrophotometer was used at 2930 cm⁻¹. -1 2960 cm -1 and 3030cm -1 The absorbance of the extract was measured at wavenumber, and the oil content of the water sample was calculated according to the three-wavenumber method specified in HJ 637-2018.

[0132] The suspended solids content was determined according to GB / T 11901-1989 "Determination of Suspended Solids in Water - Gravimetric Method", using the filtration-drying and weighing method.

[0133] The guar gum content was determined using the anthrone-sulfuric acid colorimetric method: an appropriate amount of water sample was taken, anthrone-sulfuric acid colorimetric reagent was added, the sample was heated in a boiling water bath to develop color, and then cooled to room temperature. The absorbance was measured at a wavelength of 620 nm. A series of standard solutions were prepared using guar gum standards and a standard curve was established. The guar gum content in the water sample was calculated based on the standard curve.

[0134] The residual persulfate content was determined using the iodometric method, referring to the principle of the iodometric method for determining ammonium persulfate content in GB / T 23939-2009 "Industrial Ammonium Persulfate". A suitable amount of water sample (preferably 5-20 mL of 0.01 mol / L sodium thiosulfate standard solution consumed) was placed in a 250 mL iodine flask. 2 mL of 100 g / L potassium iodide solution and 1 mL of sulfuric acid solution (1+9) were added. The flask was capped, shaken well, and allowed to stand in the dark for 15 min to allow the residual persulfate to fully react with iodide ions to form elemental iodine. Using 10 g / L starch solution as an indicator, titration was performed with 0.01 mol / L sodium thiosulfate standard solution until the blue color just disappeared, which is the endpoint. Simultaneously, a blank test was conducted using an equal volume of deionized water instead of the water sample. The residual persulfate content in the water sample was calculated using the following formula:

[0135] c = (V1 − V0) × C × M / (2 × V)

[0136] In the formula: c is the residual persulfate content in the water sample (calculated as ammonium persulfate, mg / L); V1 is the volume of sodium thiosulfate standard solution consumed in the sample titration (mL); V0 is the volume of sodium thiosulfate standard solution consumed in the blank test (mL); C is the concentration of sodium thiosulfate standard solution (mol / L); M is the molar mass of ammonium persulfate (228.20 g / mol); V is the water sample volume (L).

[0137] The removal rate of each pollution indicator is calculated according to the following formula:

[0138] Removal rate = (Indicator value before treatment - Indicator value after treatment) ÷ Indicator value before treatment × 100%.

[0139] The viscosity reduction rate is calculated using the following formula:

[0140] Viscosity reduction rate = (viscosity before treatment - viscosity after treatment) ÷ viscosity before treatment × 100%.

[0141] Table 1 Water quality indicators before and after treatment in Examples 1-3

[0142]

[0143] Table 2 Pollutant removal rates in Examples 1-3

[0144]

[0145] Tables 1 and 2 list the treatment results of Examples 1-3. After adopting stepwise pH control and sequential addition of reagents, the viscosity, COD, oil content and suspended solids content of fracturing flowback fluids with different levels of contamination were reduced simultaneously.

[0146] In Example 1, COD decreased from 3587 mg / L to 75 mg / L, with a removal rate of 97.91%; oil content decreased from 110 mg / L to 3.0 mg / L, with a removal rate of 97.27%; and suspended solids content decreased from 320 mg / L to 6.7 mg / L, with a removal rate of 97.91%. Simultaneously, guar gum content decreased from 1765 mg / L to 36.5 mg / L, indicating that acidification demulsification and activated persulfate oxidation can effectively disrupt the emulsion system in fracturing flowback fluid and degrade guar gum-like high-molecular-weight pollutants.

[0147] The COD, oil content, and suspended solids content of the flowback fluids used in Examples 2 and 3 were higher than those in Example 1. After treatment, the COD removal rates of the two groups of flowback fluids still reached 92.78% and 91.67%, respectively, and the suspended solids removal rates reached 96.86% and 95.84%, respectively, indicating that the treatment process of the present invention can be applied to fracturing flowback fluids with different pollution loads.

[0148] Test Example 2

[0149] Impact of different treatment stages on the overall treatment effect

[0150] Using the fracturing flowback fluid used in Example 1 as the test object, the treatment results of Example 1 were compared with those of Comparative Examples 1-5.

[0151] Example 1 and the comparative examples used the same batch of fracturing flowback fluid with an initial viscosity of 4.21 mPa·s, an initial COD of 3587 mg / L, an initial oil content of 110 mg / L, and an initial suspended solids content of 320 mg / L.

[0152] The detection methods for each indicator are the same as those in Test Example 1.

[0153] Table 3 Water quality indicators after treatment in Example 1 and Comparative Examples 1-5

[0154]

[0155] Table 4. Processing efficiency of Example 1 and Comparative Examples 1-5

[0156]

[0157] The results from Example 1 and Comparative Example 1 show that after eliminating the acidification and demulsification step, the oil removal rate decreased from 97.27% to 18.27%, the COD removal rate decreased to 64.15%, and the viscosity reduction rate also decreased significantly. This indicates that adjusting the pH of the system to the acidic range is beneficial for disrupting the stable interface formed by emulsified oil droplets and polymers in the backflow liquid, creating conditions for subsequent oxidation and flocculation.

[0158] As shown in Comparative Example 2, without adding ammonium persulfate, the COD removal rate was only 56.40%, significantly lower than that in Example 1, even with the acidification, neutralization, and flocculation steps retained. This indicates that relying solely on acidification demulsification and flocculation is insufficient to fully remove dissolved or dispersed organic polymeric pollutants, and that ammonium persulfate oxidative degradation is a crucial step in reducing COD and the viscosity of the backflow solution.

[0159] As shown in Comparative Example 3, when anionic polyacrylamide was added directly in an acidic environment without pH adjustment after the oxidation reaction, the removal efficiency of COD, oil content, and suspended solids was lower than that in Example 1. This indicates that adjusting the system from acidic to a neutral to alkaline environment (pH 7-9) can generate fine precipitates of carbonates and hydroxides, and cause iron ions to hydrolyze to form ferric hydroxide coagulation nuclei, thereby enhancing subsequent flocculation.

[0160] As shown in Comparative Example 4, although the oxidation and neutralization processes can reduce COD without the addition of anionic polyacrylamide, the oil content and suspended solids removal rates are only 57.91% and 79.47%, respectively. This indicates that anionic polyacrylamide can play an adsorption bridging and sweeping role between ferric hydroxide coagulation nuclei and fine precipitates, promoting the formation of larger and denser flocs from fine particles.

[0161] Comparative Example 5, with all reagents added at once, achieved a COD removal rate of 17.03% and a viscosity reduction rate of 10.93%. The simultaneous addition of citric acid, sodium carbonate, and sodium hydroxide weakened the acidification and demulsification conditions; the simultaneous contact of ammonium persulfate, ferrous sulfate heptahydrate, and alkaline components also affected the activation and oxidation process. These data indicate that staged pH adjustment and control of the order of component addition are necessary conditions for obtaining comprehensive treatment effects.

[0162] Test Example 3

[0163] The effect of iron-polymer composite on treatment effect

[0164] Examples 1, 4, and 6 were used as test subjects. All three groups of experiments used the same batch of fracturing flowback fluid, with a treatment volume of 100 mL, an initial pH of 7.2, an initial viscosity of 4.21 mPa·s, an initial COD of 3587 mg / L, an initial oil content of 110 mg / L, an initial suspended solids content of 320 mg / L, and an initial guar gum content of 1765 mg / L.

[0165] pH, viscosity, COD, oil content, suspended solids content, guar gum content, and residual persulfate content were determined according to the method described in Test Example 1.

[0166] Table 5. Processing results of Examples 1, 4 and Comparative Example 6

[0167]

[0168] Table 6. Processing efficiency of Example 1, Example 4 and Comparative Example 6

[0169]

[0170] As shown in Tables 5 and 6, after using the pre-formed premixed iron-polymer composite liquid in Example 4, COD, oil content, suspended solids, and guar gum were all further reduced. Specifically, the COD removal rate of Example 4 was 98.66%, the suspended solids removal rate was 98.78%, and the guar gum removal rate was 98.76%, all higher than those of Example 1.

[0171] The residual persulfate level after treatment in Example 4 was 6.8 mg / L, lower than 14.6 mg / L in Example 1 and 21.5 mg / L in Comparative Example 6. This result indicates that the iron-polymer composite treatment affects the consumption process of ammonium persulfate.

[0172] The residual persulfate in Comparative Example 6 was higher than that in Example 4. This indicates that the premixing step affects the utilization of the oxidant.

Claims

1. A pH-responsive integrated fracturing flowback fluid treatment agent, characterized in that: It includes acidification components, oxidation components, activation components, alkalization components and flocculation components that are stored independently of each other; The acidifying component is an aqueous solution of citric acid with a mass fraction of 8%-12%; The oxidizing component is ammonium persulfate; the activating component is ferrous sulfate heptahydrate; The mass ratio of ammonium persulfate to ferrous sulfate heptahydrate is 4-6:1; The alkalizing component includes anhydrous sodium carbonate and an aqueous solution of sodium hydroxide with a mass fraction of 8%-12%; The flocculant component is an anionic polyacrylamide solution; the concentration of the anionic polyacrylamide solution is 0.8-1.2 g / L.

2. The pH-responsive integrated fracturing flowback fluid treatment agent according to claim 1, characterized in that: The citric acid aqueous solution has a mass fraction of 10%, and the sodium hydroxide aqueous solution has a mass fraction of 10%.

3. The pH-responsive integrated fracturing flowback fluid treatment agent according to claim 1, characterized in that: The mass ratio of ammonium persulfate to ferrous sulfate heptahydrate is 5:

1.

4. The pH-responsive integrated fracturing flowback fluid treatment agent according to claim 1, characterized in that: The anionic polyacrylamide has a weight-average molecular weight of 12 million and a degree of hydrolysis of 25%-30%; the concentration of the anionic polyacrylamide solution is 1.0 g / L.

5. A pH-responsive integrated fracturing flowback fluid treatment agent, characterized in that: It includes acidification components, oxidation components, alkalization components, and premixed iron-polymer composite liquids that are stored independently of each other; The acidifying component is an aqueous solution of citric acid with a mass fraction of 8%-12%; The oxidizing component is ammonium persulfate; The alkalizing component includes anhydrous sodium carbonate and an aqueous solution of sodium hydroxide with a mass fraction of 8%-12%; The premixed iron-polymer composite liquid is formed by premixing a pH-responsive copolymer containing carboxyl, amide, and tertiary amine groups with ferrous ions.

6. The application of the pH-responsive integrated fracturing flowback fluid treatment agent as described in any one of claims 1-5 in fracturing flowback fluid treatment, characterized in that, Includes the following steps: S1 acidification and demulsification: The citric acid aqueous solution is added to the fracturing flowback fluid, the pH is adjusted to 3.0-4.0, and the mixture is stirred for 10-15 minutes. S2 oxidation degradation involves adding ammonium persulfate and ferrous sulfate heptahydrate to the acidified fracturing flowback fluid and reacting at 20-30℃ for 30-45 min. Alternatively, oxidative degradation can be achieved by adding ammonium persulfate to the acidified fracturing flowback fluid, along with a premixed iron-polymer composite solution, and reacting at 20-30°C for 30-45 minutes. S3 neutralization adjustment involves first adding anhydrous sodium carbonate to the oxidized fracturing flowback fluid, followed by an aqueous sodium hydroxide solution, to adjust the pH to 7.0-9.

0. S4 flocculation separation: Anionic polyacrylamide solution is added to the neutralized fracturing flowback fluid, and rapid stirring, slow stirring and static sedimentation are performed in sequence to separate the supernatant; Alternatively, flocculation separation can be performed without adding flocculant, followed by rapid stirring, slow stirring, and static sedimentation to separate the supernatant.

7. The application according to claim 6, characterized in that: Add 3-5 g of ammonium persulfate and 0.6-1.0 g of ferrous sulfate heptahydrate to every 1 L of fracturing flowback fluid.

8. The application according to claim 6, characterized in that: Add 5-10 g of anhydrous sodium carbonate and 10-18 mL of the sodium hydroxide aqueous solution to each 1 L of fracturing flowback fluid; control the temperature below 30℃ during the feeding process, and adjust the pH to 7.4-8.1 after the feeding is completed.

9. The application according to claim 6, characterized in that: Add 3-5 g of ammonium persulfate and 20-30 mL of the premixed iron-polymer composite solution to each 1 L of fracturing flowback fluid; in the premixed iron-polymer composite solution, the mass concentration of the pH-responsive copolymer is 1.5-2.5 g / L, and the mass concentration of ferrous sulfate heptahydrate is 30-50 g / L.

10. The application according to claim 6, characterized in that: Add 4-8 mL of the anionic polyacrylamide solution to each 1 L of fracturing flowback fluid; in step S4, first stir rapidly at 150-250 rpm for 1-2 min, then stir slowly at 40-60 rpm for 4-6 min, and then let it stand at 20-30℃ for 20-40 min to precipitate.

Citation Information

Patent Citations

  • Ferrous coordination activating persulfate system to decompose organic pollutant and citric acid application

    CN109052616A

  • Viscosity-reducing synergist, viscosity reducer and method for treating oil extraction fracturing high-viscosity wastewater

    CN117263358A